Rancang Bangun Sistem Informasi Simpanan dan Penarikan Tabungan Anggota Koperasi Aneka Usaha Mekar Jaya Cicalengka - Annisa Dwi Lestari; Encep Supriatna (Jurnal Dimamu, 2023)
The Mekar Jaya Cicalengka Aneka Usaha Cooperative is engaged in Member Savings and Loans business activities. The recording of transactions is still done manually, which is recorded in members' savings books, ledgers, and recapitulated in Microsoft Excel. The system is considered ineffective where the information needed, such as member savings reports, cannot be presented immediately if needed at any time for management purposes. To streamline the data processing of savings and withdrawals for members of the Mekar Jaya Cicalengka Aneka Usaha Cooperative, the authors designed a savings and withdrawal information system. To design the system the authors use the System Development Life Cycle (SDLC) method, namely the system development life cycle using the waterfall model. With this system built, the process of deposit and withdrawal transactions is easy to do and reports on members' deposits, withdrawals and deposit balances can be generated quickly whenever needed.